Functional Role of pX Open Reading Frame II of Human T-Lymphotropic Virus Type 1 in Maintenance of Viral Loads In Vivo - Bartoe, Joshua T. (American Society for Microbiology, 2000)
Human T-lymphotropic virus type 1 (HTLV-1) causes adult T-cell leukemia/lymphoma and is associated with a variety of immune-mediated disorders. The role of four open reading frames (ORFs), located between env and the 3′ long terminal repeat of HTLV-1, in mediating disease is not entirely clear. By differential splicing, ORF II encodes two proteins, p13(II) and p30(II), both of which have not been functionally defined. p13(II) localizes to mitochondria and may alter the configuration of the tubular network of this cellular organelle. p30(II) localizes to the nucleolus and shares homology with the transcription factors Oct-1 and -2, Pit-1, and POU-M1. Both p13(II) and p30(II) are dispensable for infection and immortalization of primary human and rabbit lymphocytes in vitro. To test the role of ORF II gene products in vivo, we inoculated rabbits with lethally irradiated cell lines expressing the wild-type molecular clone of HTLV-1 (ACH.1) or a clone containing selected mutations in ORF II (ACH.30/13.1). ACH.1-inoculated animals maintained higher HTLV-1-specific antibody titers than animals inoculated with ACH.30/13.1. Viral p19 antigen was transiently detected in ex vivo cultures of peripheral blood mononuclear cells (PBMC) from only two ACH.30/13.1-inoculated rabbits, while PBMC cultures from all ACH.1-inoculated rabbits routinely produced p19 antigen. In only three of six animals exposed to the ACH.p30(II)/p13(II) clone could provirus be consistently PCR amplified from extracted PBMC DNA and quantitative competitive PCR showed the proviral loads in PBMC from ACH.p30(II)/p13(II)-infected rabbits to be dramatically lower than the proviral loads in rabbits exposed to ACH. Our data indicate selected mutations in pX ORF II diminish the ability of HTLV-1 to maintain high viral loads in vivo and suggest an important function for p13(II) and p30(II) in viral pathogenesis.